Suicide rates during social crises: Changes in the suicide rate in Japan after the Great East Japan earthquake and during the COVID-19 pandemic. (August 2021) - Osaki, Yoneatsu; Otsuki, Hitoshi; Imamoto, Aya; Kinjo, Aya; Fujii, Maya; Kuwabara, Yuki; Kondo, Yoko; Suyama, Yoshiko
Abstract: We aimed to observe the changes in suicide rates after the Great East Japan Earthquake and during the coronavirus (COVID-19) pandemic, as typical cases of social crises, in Japan. A descriptive epidemiological study was conducted using data on the number of deaths by suicide published by the National Police Agency. The suicide rate ratio during the crisis—the monthly suicide mortality rate in the year of the crisis divided by the average suicide mortality rate in the three years before the crisis—was used as the indicator. After the earthquake, in March 2011 the suicide rate was 18% lower than the average mortality rate for the previous three years. However, it increased by 18% in May and 8% in June; increased mortality was observed among women. The suicide rate began to decline after October 2011. During the COVID-19 pandemic, the suicide rate decreased from February to June 2020. The declines in April and May were significant at 20% and 18%, respectively. From July onwards, the suicide rate of women began to rise, and from October, the overall suicide also began to increase. The rise in female suicide rates was significant, especially in October, with an increase of 70%. Thus, during these crises, suicide rates fell temporarily but then rose, especially among women. The period of increase in suicide rates was longer during the COVID-19 pandemic than after the earthquake. Therefore, there is an urgent need to promote measures for suicide prevention currently, and during a future crisis. Highlights: Suicide rates during the 2011 Earthquake and the COVID-19 pandemic were observed. Suicide rates in Japan first decreased and then increased during social crises. Suicide rates during these crises were higher among women. The increase in suicide rates during the COVID-19 pandemic lasted longer throughout the country. The increase in suicide rates after the earthquake lasted for several months in areas far from the affected areas.